The End-Diastolic Velocity of Thyroid Arteries Is Strongly Correlated with the Peak Systolic Velocity and Gland Volume in Patients with Autoimmune Thyroiditis. (14th September 2017) - Bianchini Höfling, Danilo; Marui, Suemi; Buchpiguel, Carlos Alberto; Cerri, Giovanni Guido; Chammas, Maria Cristina
Abstract : Background . The end-diastolic velocity (EDV) of thyroid arteries reflects peripheral blood flow resistance. Objective . The aim was to evaluate EDV correlations with other Doppler sonography parameters and with clinical and biochemical variables in a sample of patients with hypothyroidism caused by chronic autoimmune thyroiditis (CAT). Methods . A sample of 48 CAT hypothyroid patients receiving treatment with stable doses of levothyroxine was selected. The participants underwent clinical evaluation and measurement of serum thyrotropin (TSH), total triiodothyronine (T3), total thyroxine (T4), free T4, thyroid peroxidase antibodies (anti-TPO), and antithyroglobulin antibodies (anti-Tg) and Doppler sonography. Results . The EDV of the inferior thyroid arteries (ITA-EDV) was strongly and positively correlated with the peak systolic velocity of the inferior thyroid arteries (ITA-PSV, r = 0.919 ), thyroid volume (r = 0.711 ), and thyroid visual vascularization pattern (TVP, r = 0.687 ). There was no correlation between ITA-EDV and the clinical variables, hormones, anti-TPO, or anti-Tg. Conclusion . The strong correlation of ITA-EDV with ITA-PSV, TVP, and volume suggests that increased vascularization in CAT may be associated with a reduction in thyroid blood flow resistance, possibly due to an angiogenesis-induced increase in the total vascular cross-sectional area of the parenchyma.